THE STUDY OF QUALITY SENSORY AND MICROBIOLOGICAL VARIOUS TYPES OF SMOKED FISH WHICH MARKETED AT KECAMATAN SUKAJADI PEKANBARU - Naibaho, Nasib; Hasan, Bustari; Karnila, Rahman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was to determine evaluate the sensory quality and microbiological various types of smoked fish which marketed at Kecamatan Sukajadi Pekanbaru. Three types of smoked fish obtained from market Cikpuan, Palapa and Kodim. Smoked fish originated from Bangkinang, Pelalawan, Rokan Hilir and Palembang. Smoked fish observed to the sensory quality ang microbiological. The result of this study have shown that the sensory quality and microbiological which marketed in Palapa have the highest sensory quality from Cikpuan and Kodim; Based on the types fish which marketed have shown that selais fish have the highest sensory quality from patin and baung; Based on the origin of the production area, showed that Pelalawan have the highest sensory quality from Bangkinang, Palembang and Rokan Hilir. Based on microbiological parameter (TPC, Stapylococcus aureus, Koliform and Jamur), showed that smoked fish which marketed in Cikpuan have the highest microbiological value from Kodim and Palapa. Based on the types, the fish which marketed in the three of market showed that baung fish have the highest microbiological value from patin and selais; Based on the origin of the production area showed that Palembang have the highest microbiological from Pelalawan, Bangkinang and Rokan Hilir.Keyword : smoked fish patin, baung, selais, sensory quality, microbiological